Cultural background and diversity: N’golo and Capoeira in play - de Paula Machado Pasqua, Lívia; de Toledo, Eliana (Frontiers in Psychology, 2025)
IntroductionCapoeira is an Afro-Brazilian polysemic cultural manifestation, commonly known as fight-game formerly practiced only in streets and restricted environments and currently in training centers, gyms, and mainly in schools. The main question is: how this practice that was marginalized, prohibited by the Brazilian Penal Code in the past, can today promote an improvement in interpersonal relationships and cultural diversity among people?MethodologyThis is a documentary research characterized by a historical approach, based on capoeira-body to understand the body narrative. Sources: analysis of N’golo drawings by the artist Neves e Sousa in Galeria Verney (Portugal).Results and discussionCategories established a priori: 1. characterization of body practice, 2. musicality and 3. body elements. In short, we argue that understanding of the African roots in Capoeira is an instrumental for promoting inclusion and representation, highlighting Cultural Diversity in Physical Education as well in people daily life, in different practical contexts of teaching, all over the world.